Resposta humoral e clínica à vacinação contra leishmaniose em cães sororreagentes - Bezerra, Lucilandia Maria (2019)
In endemic regions for visceral canine leishmaniasis (CVL), the biggest challenge currently faced is the detection of infected and asymptomatic animals, as it may be the biggest risk factor for maintenance of the infection. Therefore, the diagnosis based on more sensible and specific tests may be the possible solution to control this disease. Serological tests that can identify exposed, infected or diseased animals, such as Elisa IgG anti-Leishmania, stand out as excellent tools for detecting animals in this clinical situation in high-risk areas because of their high influence in these situations. Among the pathological clinical markers that may contribute to the detection of Leishmania infection, hematological and biochemical tests were performed. As well as the early and safe diagnosis, the treatment of infected or infectious dogs using vaccines has been of interest to researchers. In this sense, two experiments were performed. In the first, the immunotherapeutic response of a double dose anti-Leishmania vaccine (Leish-Tec®) in dogs from an endemic area for CVL was evaluated. For this purpose, 85 serum samples from asymptomatic, non-reactive and low titrated reagents (1/40 cutoff point) for RIFI tests negative to the parasitological bone marrow test were analyzed. The immune response of treated dogs was evaluated by the anti-rA2 IgG ELISA whose antigen (rA2) is part of the vaccine composition. The second evaluated the performance of a recombinant protein rK28, aiming to verify its sensitivity in detecting infected animals in endemic area. In this sense, a clinical intervention and control trial was designed to analyze the positive and negative outcomes of the animals under study. According to serological screening tests (RIFI) the animals were divided into five groups, including NRNV - unvaccinated nonreactive, n = 23; RNV - unvaccinated reagent, n = 7; NRVS - vaccinated nonreactive 1 ml, n = 22; NRVD - non-vaccinated reagent 2 ml, n = 16; and RVD - 2 ml vaccinated reagent, n = 15. After grouping, the animals were vaccinated with three applications at 21-day intervals and followed at six points of care every three months through clinical and laboratory examinations for a period of 18 months. To assess the presence or absence of parasites, bone marrow and PCR parasitological tests were performed at six and nine months after vaccination, respectively. The animal’s serological response to infection was assessed by anti-rA2 and anti-rK28 IgG levels. Hepatic and renal enzymes were tested as a condition of possible tissue damage in these organs, no changes compatible with infection or inflammation were observed, in the average of the groups in the last following point. Regarding the evaluation of responses to anti-rA2 IgG antibodies, there was a high response in the single-dose (NRVS) vaccinated groups and low response in the double dose (NRVD and RVD) vaccinated groups. When the groups were compared, there was a statistical difference between the vaccinated groups and the unvaccinated nonreactive control. The rK28 protein performed well in all groups, showing a high sensitivity in detecting positive and negative infected parasitological tests and PCR. It was concluded that the anti-leishmania vaccine (Leish-Tec®) is immunogenic by inducing high levels of anti-rA2 IgG antibodies. Double-dose vaccination reduces anti-rA2 antibody levels compared to single-dose vaccination. However, single or double dose vaccination of seropositive animals for IFAT does not provide protection against Leishmania infection. Also, detection of anti-rK28 IgG presents good performance for diagnosis of CVL in asymptomatic animals exposed in endemic area.